PENGEMBANGAN INSTRUMEN PENILAIAN KINERJA SISWA PADA PRAKTIKUM FISIKA GETARAN DI SMP - Rhys Mauludin Almuflichan (Jurnal Evaluasi Pendidikan, 2016)
The purpose of this research is to develop an instrument to measure the performance of junior high school (SMP) students on the topic "Vibration" in Physics experiments. The technique used for choosing the sample was multistage random sampling. The development of statement of items in the instrument was based on the judgments of experts and panelists. The measurement scale of the instrument is Rating Scale. The result of experts' judgments produced 20 items for the instrument. The instrument was tested twice to 190 junior high school students in Babat District, Lamongan Regency, East Java Province. The data was analyzed by using Structured Equation Modelling (SEM). First try out (testing) resulted in the exclusion of 2 items. Based on appropriate model, second try out resulted in no exclusion of items, hence the instrument os found to be fit (model fit). As two items got dropped in the first try out, the final instrument consists of total 18 items. After having tested the validity and reliability of the instrument, it can be concluded that the instrument has an appropriate construct validity and reliability. Nevertheless further try outs are still needed to standardize the instrument.